An Efficient Approach on Big Data for Stock Prediction with the Aid of Optimal Machine Learning Approach - Sameerapallavi, TP; Manjula, B (International Journal of Computer Sciences and Engineering, 2019)
The research on stock market is considered as an important issue from recent years. The investment in stock market is performed based on prediction and analysis. The current market economy has numerous variables which need to be considered before doing a transaction in stock market. So, the analysis of the variables manually is a tough task. In order to predict the variables in the stock market and analyse the affecting factors machine learning approach is best suited. The machine learning can provide prediction of different aspects such as index value, higher stock price, exchange rate etc. Different machine learning approaches like naive Bayes classifier, support vector machine, Artificial neural networks are reviewed which helps in stock price prediction and the market prediction. stock market prediction helps the investors and traders make better and quick decisions and ensure profits. Furthermore, advantages and limitations are discussed based on the prediction accuracy and performance.